# Chapter 2.Polynomials

1.Important Identities of Polynomials

1. (x + y) ² = x² + 2xy + y²

2 .(x y) ² = x² – 2xy + y²

3. x² – y² = (x + y) (x y)

2.Use of Polynomial Identities

1) factorisation.

2.find out  Square of Big Numbers

3.Remainder Theorem

4. Factor Theorem

Example:- ax+b+c=0   is monomial , degree of x is 1

ax²+bx+c=0 is Binomial (or Quadratic Polynomial) , degree of x is 2

ax3+ax²+bx+c=0 is cubic Polynomial, degree of x is 3.

3.Remainder Theorem : Let p(x) be any polynomial of degree greater than or

equal to one and let a be any real number. If p(x) is divided by the linear

polynomial x – a, then the remainder is p(a).

Proof : Let p(x) be any polynomial with degree greater than or equal to 1. Suppose

that when p(x) is divided by x a, the quotient is q(x) and the remainder is r(x), i.e.,

p(x) = (x a) q(x) + r(x)

Since the degree of x a is 1 and the degree of r(x) is less than the degree of x a,

the degree of r(x) = 0. This means that r(x) is a constant, say r.

So, for every value of x, r(x) = r.

Therefore, p(x) = (x a) q(x) + r

In particular, if x = a, this equation gives us

p(a) = (a a) q(a) + r

= r,

which proves the theorem.

4. Factor Theorem : If p(x) is a polynomial of degree n > 1 and a is any real number,

then (i) x a is a factor of p(x), if p(a) = 0, and (ii) p(a) = 0, if x a is a factor of p(x).

Proof: By the Remainder Theorem, p(x)=(x a) q(x) + p(a).

(i) If p(a) = 0, then p(x) = (x a) q(x), which shows that x a is a factor of p(x).

(ii) Since x – a is a factor of p(x), p(x) = (x a) g(x) for same polynomial g(x).

In this case, p(a) = (a a) g(a) = 0.

5. Factorisation of the polynomial ax2 + bx + c by splitting the middle term is as

follows:

Let its factors be (px + q) and (rx + s). Then

ax2 + bx + c = (px + q) (rx + s) = pr x2 + (ps + qr) x + qs

Comparing the coefficients of x2, we get a = pr.

Similarly, comparing the coefficients of x, we get b = ps + qr.

And, on comparing the constant terms, we get c = qs.

This shows us that b is the sum of two numbers ps and qr, whose product is

(ps)(qr) = (pr)(qs) = ac.

Therefore, to factorise ax2 + bx + c, we have to write b as the sum of two

numbers whose product is ac.

6. Algebraic Identities

Identity I: (a + b)2 = a2 + 2ab + b2

Identity II: (a – b)2 = a2 – 2ab + b2

Identity III: a2 – b2= (a + b)(a – b)

Identity IV: (x + a)(x + b) = x2 + (a + b) x + ab

Identity V: (a + b + c)2 = a2 + b2 + c2 + 2ab + 2bc + 2ca

Identity VI: (a + b)3 = a3 + b3 + 3ab (a + b)

Identity VII: (a – b)3 = a3 – b3 – 3ab (a – b)

Identity VIII: a3 + b3 + c– 3abc = (a + b + c)(a2 + b2 + c2 – ab – bc – ca)

Summary of this chapter

1. A polynomial p(x) in one variable x is an algebraic expression in x of the form

p(x) = anxn + an–1xn – 1 + . . . + a2x2 + a1x + a0,

where a0, a1, a2, . . ., an are constants and an ¹ 0.

a0, a1, a2, . . ., an are respectively the coefficients of x0, x, x2, . . ., xn, and n is called the degree

of the polynomial. Each of anxn, an–1 xn–1, …, a0, with an ¹ 0, is called a term of the polynomial

p(x).

2. A polynomial of one term is called a monomial.

3. A polynomial of two terms is called a binomial.

4. A polynomial of three terms is called a trinomial.

5. A polynomial of degree one is called a linear polynomial.

6. A polynomial of degree two is called a quadratic polynomial.

7. A polynomial of degree three is called a cubic polynomial.

8. A real number ‘a’ is a zero of a polynomial p(x) if p(a) = 0. In this case, a is also called a

root of the equation p(x) = 0.

9. Every linear polynomial in one variable has a unique zero, a non-zero constant polynomial

has no zero, and every real number is a zero of the zero polynomial.

10. Remainder Theorem : If p(x) is any polynomial of degree greater than or equal to 1 and p(x)

is divided by the linear polynomial x a, then the remainder is p(a).

11. Factor Theorem : x a is a factor of the polynomial p(x), if p(a) = 0. Also, if x a is a factor

of p(x), then p(a) = 0.

12. (x + y + z)2 = x2 + y2 + z2 + 2xy + 2yz + 2zx

13. (x + y)3 = x3 + y3 + 3xy(x + y)

14. (x y)3 = x3 – y3 – 3xy(x y)

15. x3 + y3 + z3 – 3xyz = (x + y + z) (x2 + y2 + z2 – xy yz zx)

You have successfully subscribed to the newsletter

There was an error while trying to send your request. Please try again.

EduInfoshare will use the information you provide on this form to be in touch with you and to provide updates and marketing.